Surface-dependent magnetic behavior of α-Fe2O3 quasi-cubes induced by Mg2+ ions1. Issue 37 (7th October 2015) - Liu, Rongmei; Jiang, Zixiang; Liu, Qi; Zhu, Xiandong; Yan, Zhiyang; Chen, Weiye
<x xml:space="preserve">Abstract</x> α-Fe2O3 quasi-cubes with high-index facets exposed were synthesized in a controlled manner by Mg2+ ions, and show surface-dependent magnetic behavior.